COVID-19: Experiences of Social Workers Supporting Older Adults With Dementia in Nigeria - Oluwagbemiga Oyinlola MSW, MSc; Kafayat Mahmoud PhD; Abdullateef B. Adeoti PhD; Adewole A. Abiodun MSW (SAGE Publishing, 2024)
Amidst the COVID-19 pandemic, numerous public health protocols were instituted by government agencies to safeguard individuals with dementia, their family caregivers, and formal care providers. While these preventive measures were implemented with good intentions, they inadvertently imposed significant challenges on medical social workers in Nigeria. This paper explored the experiences of medical social workers caring for people with dementia during the COVID-19 pandemic in Nigeria. Twenty-six medical social workers from 6 government hospitals in Southwestern Nigeria participated in an in-depth interview. The research reveals 3 pivotal aspects: Firstly, the escalating demands within the work environment, where medical social workers grapple with the intricate task of conveying sensitive information about dementia diagnosis and COVID-19 prevention protocol, managing expectations regarding dementia diagnoses, and navigating resource constraints for individuals with dementia during the pandemic. Secondly, discernible impacts on the work climate and interprofessional relationships shed light on the challenges these professionals face in collaborating with other healthcare providers. Lastly, the reverberations on social workers' personal lives underscore the pandemic's toll on their well-being. Thus, the findings underscore the need for proactive measures to equip medical social workers to face the distinctive challenges in dementia care during future pandemics. Recognizing the potential resurgence of global health crises, the research highlights the need for strategic preparedness to mitigate the impact of future pandemics on the well-being of individuals with dementia and the professionals dedicated to their care.